The filmmaker's guide to creatively embracing limitations : not getting what you want leading to creating what you need - Pace, William (Faculty associate of digital media production); Stobbe, Ingrid (Routledge, 2023)
"Starting out as a filmmaker comes with a whole host of limitations and challenges that lead to one key question: how do you channel your creativity within these limitations to create a compelling and impactful film? Authors William Pace and Ingrid Stobbe provide both historical and contemporary examples to provide context for filmmaking successes, as well outlining practical exercises filmmakers can apply to their own creative processes. Looking into limitations and restrictions that arise at all stages of the film production process, the book illuminates the importance of developing unique creative muscles and how to apply this potential to your own work. This is a unique text in the field that provides both a theoretical and practical approach to inspired and savvy filmmaking. Drawing on examples from Frank Oz, Pete Docter, Chloé Zhao, and Lee Isaac Chung, filmmakers will gain a well-rounded understanding of the creative processes behind narrative production and how to shape their own independent creative by encouraging budget-conscious and creatively aware filmmaking. Foregrounding strategy and capability, making a film for the first time is no longer overwhelming with this highly practical textbook. Ideal for undergraduate students of film production and first-time filmmakers"--